Kematian Yang Mematikan: Keberhasilan Misi Simson dalam Hakim-hakim 16 - Prabowo, Paulus Dimas (Jurnal Apokalupsis, 2023)
Samson was one of the judges who ruled Israel in the pre-monarchy era. He was called to carry out a mission, namely to start saving Israel from the Philistines. His personal uniqueness lay in his superpowers, apostolic status, and a fleshly controlled lifestyle. Not a few writers have observed it and concluded that its mission failed. However, did Samson really fail because his lifestyle was not ideal? This article proves that Samson's mission was not a failure even though his motivation and methods were not ideal, because there is God's intervention in it. Through the method of narrative literary exegesis which involves structural analysis, style analysis, editorial analysis, exegetical analysis and theological analysis, the fact is that Samson's mission was successful. The defeat of the Philistines and the fall of Dagon's temple in 16:23-31 has been stated implicitly in 16:1-3. The number of enemies killed is increased. This data shows that Samson's mission was a success.